2012
DOI: 10.5194/npg-19-165-2012
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence in a global magnetohydrodynamic simulation of the Earth's magnetosphere during northward and southward interplanetary magnetic field

Abstract: Abstract. We report the results of MHD simulations of Earth's magnetosphere for idealized steady solar wind plasma and interplanetary magnetic field (IMF) conditions. The simulations feature purely northward and southward magnetic fields and were designed to study turbulence in the magnetotail plasma sheet. We found that the power spectral densities (PSDs) for both northward and southward IMF had the characteristics of turbulent flow. In both cases, the PSDs showed the three scale ranges expected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Several studies [ Wiltberger et al ., ; El‐Alaoui , ; Ashour‐Abdalla et al ., ; Walker et al ., ; El‐Alaoui et al ., ; Birn et al ., ; Ge et al ., ] have revealed that earthward flow from a tail neutral line reversed direction in the inner magnetosphere to form a large‐scale vortex. These flow channels therefore drove vortices that appeared to drive MHD turbulence [ El‐Alaoui et al ., , , ; Wiltberger et al ., ]. From a global simulation point of view these localized high speed flows have been described as regions of low flux tube entropy [ Birn et al ., ; Dubyagin et al ., ; El‐Alaoui et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [ Wiltberger et al ., ; El‐Alaoui , ; Ashour‐Abdalla et al ., ; Walker et al ., ; El‐Alaoui et al ., ; Birn et al ., ; Ge et al ., ] have revealed that earthward flow from a tail neutral line reversed direction in the inner magnetosphere to form a large‐scale vortex. These flow channels therefore drove vortices that appeared to drive MHD turbulence [ El‐Alaoui et al ., , , ; Wiltberger et al ., ]. From a global simulation point of view these localized high speed flows have been described as regions of low flux tube entropy [ Birn et al ., ; Dubyagin et al ., ; El‐Alaoui et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Muñoz et al: Fractality in space plasmas (Kadanoff et al, 1995;Pisarenko et al, 1993), and the solar wind (Chapman et al, 2008); but it is interesting to note that it does describe some relevant features of these time series' complexity, as it has been successfully used in previous works relevant to the Sun-Earth system (Osella et al, 1997;Kozelov, 2003;Gallagher et al, 1998;Georgoulis, 2012;Lawrence et al, 1993;Cadavid et al, 1994;McAteer et al, 2005). We will thus use the box-counting as a fast approach and a first step to detect universal features worth further study.…”
mentioning
confidence: 99%
“…Evidence of turbulence in the Earth's magnetosphere has been found by various spacecraft observations (Nykyri et al, 2006;Sundkvist et al, 2005;Zimbardo et al, 2008), and several authors have studied magnetospheric MHD turbulence (see, e.g., Borovsky, 2004;Hwang et al, 2011;El-Alaoui et al, 2012). However, given the large number of degrees of freedom, simulation of turbulent systems has a large computational cost, which has led to the development of analytical models, which, while sharing statistical properties of the systems under study, depend only on a few degrees of freedom (Chapman et al, 1998;Valdivia et al, 2006).…”
mentioning
confidence: 99%
“…By comparing in situ observations to simulation results we hope to find out how the properties of turbulence depend on overall conditions. Eventually, MHD can be combined with kinetic studies to quantify the overall dissipation over both inertial and dissipative scales and how turbulence influences reconnection (Lapenta 2008;Kowal and Lazarian 2010;El-Alaoui et al 2012. Studies using MMS data will probe further how turbulence changes the reconnection process and can affect the reconnection rate Lamkin 1985, 1986;Goldstein et al 1986;Strauss 1988;Klimas et al 2010;Eyink et al 2011).…”
Section: Reconnection and Turbulencementioning
confidence: 99%